Tratamento de água residuária ácida proveniente de mina utilizando soro de leite como doador de elétrons - Sampaio, Gabriela Freitas (2015)
Mining activities have great economic and social importance, but lead to many environmental problems, one of the most severe the Acid Mine Drainage (AMD). The AMD comes from the oxidation of sulphide minerals, particularly pyrite, which when exposed to water and oxygen generate an effluent with high acidity, high sulfate levels and heavy metals. The chemical methods employed for the treatment of AMD have high operational costs, which makes the anaerobic biological treatment an alternative technically feasible of treatment. This process consists of sulfate reduction to hydrogen sulphide, resulting in an increase of pH and precipitation of heavy metals. For this occurs the reduced sulfate reducing bacteria (SRB), require a carbon source which may be simple substrates, such as ethanol and hydrogen. However, complex compounds can be hydrolyzed and fermented by other bacteria before their use. One of the compounds with potential for this purpose is the cheese whey. The cheese whey can be marketed as food for animals and fertilizers, however, part of this by-product is lost in the effluent from the dairy industries. In the present study, an UASB (Upflow Anaerobic Sludge Blanket) was used for the treatment of AMD using cheese whey as carbon source, simulating a real effluent. Operating in a total of 300 days, the ratio COD/SO42- and HRT applied were 1 and 24 hours, respectively. The reactor operated by 139 days with the initial operating condition for concentration of 500 mg.l-1 sulfate and COD, being obtained average efficiency of COD removal (84±7) % and sulfate removal (38±14) %. In the second phase of operation, which occurred over 91 days, the concentrations were increased to 1000 mg.l-1, and the results were (74±5) % of COD and (9 ± 74) % of sulfate removal. A further increase in concentration, decreased system efficiency, in new condition 1500 mg l-1 sulfate and COD were entered into the system, being operated over 53 days. It was obtained a removal efficiency of (68±4) % and (63±7)% of COD and sulfate, respectively. The increase in COD and SO42- concentrations gave better removal rates, according to the kinetic adjustment, of both compounds. With addition of the metals, Fe2+ 100 mg.l-1; 20 mg.l-1 Zn2+; 5 mg.l-1 Cu2+, the reactor answered positively. This condition was run for 15 days and was reached (79±7)% and (71±2)% removal of COD and sulfate respectively, with Fe removal, Cu and Zn of about 99%.